Monitoring bedfast ice and ice phenology in lakes of the Lena River Delta using TerraSAR-X backscatter and coherence time series. - Antonova, Sofia; Duguay, Claude R; Kääb, Andreas; Heim, Birgit; Langer, Moritz; Westermann, Sebastian; Boike, Julia (PANGAEA, 2016)
The goal of this study was to examine the potential of a unique X-band SAR dataset to monitor ice phenology and bedfast ice on a number of thermokarst lakes in the Siberian Arctic. Three-year repeat-pass TSX time series with high temporal (11 days) and spatial (10 m) resolution were used. Two different parameters derived from SAR imagery were employed in the analysis: backscatter intensity and 11-day interferometric coherence. In situ ice thickness measurements were collected at 14 locations from a sample of 10 lakes in April 2015. A region of interest (ROI) was created around each in situ ice thickness measurement location as a circle with a diameter of approximately 10 pixels. We provide extracted backscatter and coherence for all the ROIs as georeferenced .tif files for the entire time series.
Three-year time series of TerraSAR-X backscatter intensity and interferometric coherence for lakes in the Lena River Delta, Siberia, links to GeoTIFF images
Keywords: Dalniye Zelentsy; File format; File name; File size; Kurungnakh_Island; Lena2013; SAT; Satellite remote sensing; Uniform resource locator/link to file